Pengaruh Kompetensi dan Pelatihan terhadap Kinerja Karyawan di PT Dwipindo Karyo Mandiri - Juan Isma, Miftahul; Siska, Elmira; Indra, Natal (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2023)
The role of competence and training is very important in improving employee performance. Employees who have adequate competence will be able to carry out their work tasks better. The training provided by the company will improve employee competence so that they are able to improve their performance. This study aims to examine the effect of competence and training on employee performance at PT Dwipindo Karyo Mandiri. Methods of data collection using questionnaires distributed to 35 employee respondents with techniquesNon Probability Sampling or non-random sampling with saturated sampling (Census) and the entire population is used as a sample. The collected data were analyzed using the SPSS application. The results of the study show that competence and training have a positive and significant impact on employee performance. Competence has a positive and significant effect on employee performance with a beta coefficient of 0.781 and a t-value of 6.820. Meanwhile, training also has a positive and significant effect on employee performance with a beta coefficient of 0.087 and a t-value of 5.071. From the results of this study it can be concluded that companies should pay attention to competency development and employee training as an effort to improve employee performance. In the long term, competency development and employee training can provide benefits to companies in increasing competitiveness and business growth.